Artists and Creators. The Hard Fate of an Artist or a Story of Happy Workers? - Jeran, Agnieszka (Studia Oeconomica Posnaniensia, 2017)
Artists and creators are a specific subset of people. Analyses based on public statistical data allow to conclude significant gaps in the knowledge of this category of workers, even in the identification of their number. At the same time knowledge of their market situation, income, conditions or quality of life are small. Based on the data obtained from a study of artists and creators associated with Bydgoszcz and Torun this analysis presents the characteristics of their professional situation and data from a Social Diagnosis (from 2013) was used to expose the situation in terms of quality of life. Both studies are based on different assumptions, but their statement completes our little knowledge about artists and creators in the context of their work. It is also a prerequisite for further research.